Analisis Volume Material Dalam Upaya Meningkatkan Keakuratan Perhitungan Dengan Building Information Modeling (BIM) - Prasetyo, Bagas Dwi; Suksmono, Arif Kurniawan; Ningsih, Dewi Laras Sulastri (Proceedings Series on Physical & Formal Sciences, 2026)
The continuous growth of Indonesian population has directly led to an increased demand for infrastructure and public facilities, particularly in the construction sector. This development necessitates the adoption of effective and efficient construction technologies, one of which is Building Information Modeling (BIM). Within the BIM framework, the 3D modeling software Revit 2021 can be utilized to assess and analyze the accuracy of structural volume calculations compared to manual estimations made during the initial planning stage (Bill of Quantities/BOQ). Following the modeling process, the material quantity take-off results generated using Revit 2021 revealed a total concrete volume of 606.96 m, a total plain reinforcing steel weight of 48,004.41 kg, and a total deformed reinforcing steel weight of 57,749.20 kg. These findings indicate that the manually prepared BOQ showed a greater discrepancy compared to actual field implementation data (MC-100), with a percentage difference of +4.27% for concrete volume, -1.84% for plain steel volume, and +16.54% for deformed steel volume. In contrast, the calculations performed using Revit 2021 demonstrated a higher degree of accuracy. They were more closely aligned with field implementation results (MC-100), showing only +0.75% for concrete, +1.24% for plain steel, and -0.84% for deformed steel. Therefore, the use of Revit software can be considered a valuable tool in building modeling processes, offering more accurate volume calculations that better reflect real-world conditions.